Analisis aktivitas pembelajaran SBdP muatan seni musik pada kurikulum merdeka ditinjau dari perspektif pendidikan seni holistik kelas IV sekolah dasar - Lathifa Hasta Maullana Wibisono; Karsono Karsono; Joko Daryanto (Universitas Sebelas Maret, 2024)
This research is intended to describe and analyze the learning activities of SBdP (Seni Budaya dan Prakarya) music content in the fourth grade of the Merdeka curriculum from the perspective of holistic art education. Holistic art education encompasses three aspects: (1) mind, (2) body, and (3) spirit. This is a qualitative case study. The approach involves an intensive, detailed, and in-depth examination of the research subject to gather comprehensive information about the topic.The subjects in this study include learning activities, educators, and fourth-grade students at SD Negeri Setono. Data collection techniques include observation, interviews, document analysis, and documentation. Data validity is tested using source triangulation and techniques. Data collected are analyzed using the interactive model by Miles and Huberman with a conceptual framework based on aspects in holistic art education.The results of the research are as follows. First, the SBdP music curriculum has developed the three realms in line with holistic art education. The dominant aspect developed is in the realm of Mind (mind), while the realm of Body (physical skills) and Spirit (emotional experience) are still not well-developed. This is due to the fact that developing the body aspect requires musical equipment, while the school's musical instruments and facilities are inadequate, leading to a focus on singing instruction only. The development of the spirit aspect is also lacking due to the absence of intensive activities for appreciating musical works. Second, the learning examined in this research remains predominantly informative and does not provide experiential learning that involves emotional engagement and the development of students' faculties. This is a consequence of the school's limited resources and the capabilities of the educators.Keywords: education, music, holistic art, elementary school.